Excavation at a new Upper Palaeolithic site of the Eger region (Northern Hungary) - Mester, Zsolt (Dissertationes Archaeologicae, 2013)
In August 2013, a new site was excavated on the top of Gyilkos Hill at Andornaktálya, near Eger (Northern Hungary). This investigation belongs to a Polish–Hungarian research collaboration in the frame of which four Palaeolithic sites were excavated in the Eger region since 2002. The knapped industry collected at Andornaktálya-Gyilkos site can be attributed to the Early Upper Palaeolithic Aurignacian culture.